In Vitro Screening Potential Antibacterial Properties of the Greek Oregano Honey against Clinical Isolates of Helicobacter pylori - Voidarou, Chrysoula (Chrysa) (Foods, 2021)
Oregano honey is an exceedingly rare and distinct product, not commercially available, produced by bees bred in oregano fields of alpine altitudes at the mountainous area of Epirus, Greece. In ethnic popular medicine, this product is used as a therapeutic in various gastric diseases. To test this hypothesis, 14 strains of Helicobacter pylori (H. pylori), 6 isolated from gastric ulcers and 8 from cases of clinical gastritis, were employed in the present study. The above bacterial strains were exposed to various concentrations (75% v/v, 50% v/v, 25% v/v, 12.5% v/v, and 6% v/v) of 50 oregano honey samples by using the agar well method and the inhibition zones observed around each well were recorded. Although the inhibitory zones of the H. pylori isolated from the gastric ulcers were wide enough (0–34 mm), those strains, in general, appeared more resistant than the other eight (0–58 mm). The same result was observed when the same strains were tested against six antibiotics used in clinical practice. Extracts of oregano honey were prepared by extraction with four different organic solvents. N-hexane and chloroform extracts had the most potent antibacterial action. Finally, pure oregano honey and diethyl ether extracts of honey showed significant inhibitory activity against urease secreted by the pathogen. These results strongly indicate the susceptibility of H. pylori strains to the oregano honey by more than one mode of action. Consequently, this variety of honey seems to have potential therapeutic properties against gastric ulcers and gastritis, thus explaining the preference of the locals towards this traditional remedy.